Quantificação de danos e perdas causados pela giberela do trigo - Nunes, Johan Filipe Lima (2023)
The culture of wheat is of great importance to Brazil and the world. Wheat productivity can be affected by several factors, with diseases playing a major role Among the diseases, giberella stands out (Fusarium graminearum), that can not only lead to reduced yields but can also greatly affect grain quality due to the production of mycotoxins, which represent an enormous risk to human and animal health. The management of the disease is an enormous challenge for the world's triticulture, and is normally done using fungicides, cultivars with a certain level of resistance to the disease and cultural management practices. However, there are costs associated with the use of each management strategy. There is still a lack of scientific information on the damage (reduction in yield quantity and/or quality) and losses (reduction in financial return due to disease) caused by the disease under different management strategies. The aim of this work was to quantify the damage and losses caused by the disease in 8 management strategies (involving genetic resistance, application or not of fungicide and use or not of silicium (in the form of potassium silicate), under irrigated and rainfed cultivation conditions. The analysis involved the determination of wheat yield, total crop costs, and cost-effectiveness. Planting wheat with irrigation provided the best overall performance. The best cost-effective management of Fusarium graminearum was obtained by integrating the cultivar LG ORO with fungicide application, which provided a 30.77% reduction in disease incidence, a 20% increase in productivity, and a positive balance of R$ 7.319,66 over the control treatment. The results of this study lead to the conclusion that the choice of Fusarium graminearum management strategy affects the cost of production, making a cost-effective analysis necessary to decide on the best strategy to be adopted. Determining the damage and losses caused by the disease under different management strategies is a prerequisite for defining a rational strategy for economical management of Fusarium Head Blight in wheat.